(untitled) (Research, Society and Development, 2022)
Objective: to relate the classifications of trisomy 21 according to the number of live births in Brazilian states between 2016 and 2020. Methodology: refers to a retrospective, descriptive study of live births with T21 that occurred between 2016 and 2020 in Brazil. The information pertinent to the preparation of the study was immediately removed from the Information System on Live Births (SINASC) of the Department of Informatics of the Unified Health System (DATASUS) of the Ministry of Health (MS). Results and discussion: it can be observed, in the three classifications of Down syndrome, the state of São Paulo with the highest percentage (149 cases corresponding to 60.82%), in meiotic n-disjunction, and the lowest percentage the state of Mato Grosso do sul (1 case referring to 0.4%), it can be observed that the classification that presented the lowest percentage of live births was by moisacism, with São Paulo also having the highest percentage compared to the others (45 cases referring to 46.40%). Conclusion: this research made it possible to analyze the three classifications of trisomy at a global level, and pointed out the need to collect primaries data that, as they come from existing database systems, depend on the quality of filling out the notification forms, and new research related to the theme.